Dental trauma and its association with anatomic, behavioral, and social variables among fifth and sixth grade schoolchildren in Jerusalem - Sgan-Cohen HD, Megnagi G, Jacobi Y. (Blackwell Synergy, 2005)
With the decrease in dental caries prevalence, public health should place emphasis on other dental diseases.